ROCK. Co-design workshops and self-built transformation of public space in Bologna with students and professionals. Urban regeneration of Piazza Scaravilli. The Malerbe experience - Leoni, Giovanni; Longo, Danila; Boeri, Andrea; Gianfrate, Valentina; Bonoli, Alessandra; Gaspari, Jacopo; Antonini, Ernesto; Vai, Elena; Pollastri, Marco; Mercuri, Riccardo; Branchini, Sara (Alma Mater Studiorum - Università di Bologna, 2021)
The dataset contains the presentation and preparatory materials presented within the co-design workshop and self-built transformation of public space “Malerbe” held in June-July 2017 in Bologna, and the project of urban regeneration of Piazza Scaravilli co-developed by students and professionals during this workshop. It is within this experience that ROCK “co-design co-construction workshop and self-built transformation of public space” format has been developed. From this experience several other workshops have then been organized during ROCK project, to develop projects of urban regeneration in Bologna university district, along Via Zamboni. Data collected in this dataset contain project proposals developed in a co-design workshop with University of Bologna architecture and design students, University of Bologna researchers, Centro Antartide staff. The projects are meant to be temporary installations to be realized by the same students in Piazza Scaravilli, previously a parking space. Data can be used by both university researchers (as methodology to be replicated in similar workshops) or by city staff to take inspiration for projects to be realized in similar parts of the city.